Lemmus sibiricus FJ - Spitsyn, Vitaly M.; Bolotov, Ivan N.; Kondakov, Alexander V.; Klass, Anna L.; Mizin, Ivan A.; Tomilova, Alena A.; Zubrii, Natalia A.; Gofarov, Mikhail Y. (Zenodo, 2021)
Siberian Lemming Lemmus sibiricus (Kerr, 1792) Type locality: The northern parts of the Uralian chain of mountains, and on the river Oby [ cytb sequence of a topotype: AJ012671] (Kerr 1792; Fedorov et al. 1999). Synonyms: L. obensis Brants, 1827 [TL: Mouth of the Obi River, Siberia, Russia] (Ellerman 1949; Hinton 1926); L. obensis bungei Vinogradov, 1926 [TL: Mostakh Island near the Lena River mouth, Yakutia, Russia; cytb sequence of a topotype: FJ025981] (Abramson et al. 2008; Baranova & Gromov 2003); L. sibiricus West Palearctic sensu Abramson et al ., 2008 (Abramson et al. 2008). Distribution: Euro-Siberian Arctic species. Arctic Europe east of the Kola Peninsula and Arctic Siberia up to the Lena Delta (Abramson et al. 2008; Abramson & Petrova 2018). Comments: L. obensis was considered a junior synonym of Kerr’s taxon based on a close proximity of the type localities and morphological data (Ellerman 1949). This solution was confirmed on the basis of molecular genetic research (Abramson et al. 2008). Topotypes of L. obensis bungei were considered belonging to L. sibiricus based on DNA sequence data (Abramson et al. 2008). Published as part of Spitsyn, Vitaly M., Bolotov, Ivan N., Kondakov, Alexander V., Klass, Anna L., Mizin, Ivan A., Tomilova, Alena A., Zubrii, Natalia A. & Gofarov, Mikhail Y., 2021, A new Norwegian Lemming subspecies from Novaya Zemlya, Arctic Russia, pp. 93-117 in Ecologica Montenegrina 40 on page 115, DOI:10.37828/em.2021.40.8, http://zenodo.org/record/13233031